2019
DOI: 10.12800/ccd.v14i42.1334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle strength training in postmenopausal women with metabolic syndrome. Systematic review

Abstract: During menopause, the risk of developing metabolic syndrome increases exponentially because of hormonal changes and old age. The aim is to perform a systematic review of randomized clinical trials to the effects of muscle strength training on the different parameters of the metabolic syndrome in postmenopausal women. A systematic review of the literature was performed in Pubmed, ScienDirect and SportDiscus using the words: Resistance training and metabolic syndrome or strength training and menopause, giving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(83 reference statements)
1
0
0
Order By: Relevance
“…The clinical trials carried out by Cinar N, which in cludes early rehabilitation from the first postoperative day (Cinar et al, 2008), Eyigor S that involved pilates exercises (Eyigor et al, 2010), Lindquist H in a population with lymphedema after mastectomy (Lindquist et al, 2015), and Wingate L who applied as treatment a combination of exercises in hospitalization and others at home, reported that these strategies were related to the recovery of functional capacity in women with breast cancer, which supports what was presented by other authors who point out that involving exercise in rehabilitation processes of this population is beneficial (Volaklis et al, 2013;Yuen & Sword, 2007), especially in the function of the shoulder, if you work through structured exercise plans (McNeely et al, 2010). Exercise has been described as having multiple benefits at cardiovascular, metabolic and bone health in general population (Colado et al, 2020;Gómez-Álvarez et al, 2019) and in women with breast cancer (Kirkham et al, 2016;Volaklis et al, 2013) and that even the type of exercise that is performed determines the degree of recovery, finding better results with resistance exercise compared to aerobic exercise (Yuen & Sword, 2007), among other reasons because it has been found to help regain muscle strength and reduce fatigue symptoms related to treatments, which in turn helps improve the ability to carry out activities of daily living (Volaklis et al, 2013).…”
Section: Discussionsupporting
confidence: 69%
“…The clinical trials carried out by Cinar N, which in cludes early rehabilitation from the first postoperative day (Cinar et al, 2008), Eyigor S that involved pilates exercises (Eyigor et al, 2010), Lindquist H in a population with lymphedema after mastectomy (Lindquist et al, 2015), and Wingate L who applied as treatment a combination of exercises in hospitalization and others at home, reported that these strategies were related to the recovery of functional capacity in women with breast cancer, which supports what was presented by other authors who point out that involving exercise in rehabilitation processes of this population is beneficial (Volaklis et al, 2013;Yuen & Sword, 2007), especially in the function of the shoulder, if you work through structured exercise plans (McNeely et al, 2010). Exercise has been described as having multiple benefits at cardiovascular, metabolic and bone health in general population (Colado et al, 2020;Gómez-Álvarez et al, 2019) and in women with breast cancer (Kirkham et al, 2016;Volaklis et al, 2013) and that even the type of exercise that is performed determines the degree of recovery, finding better results with resistance exercise compared to aerobic exercise (Yuen & Sword, 2007), among other reasons because it has been found to help regain muscle strength and reduce fatigue symptoms related to treatments, which in turn helps improve the ability to carry out activities of daily living (Volaklis et al, 2013).…”
Section: Discussionsupporting
confidence: 69%